-5(3t-4)+4t=6t-8

Simple and best practice solution for -5(3t-4)+4t=6t-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(3t-4)+4t=6t-8 equation:


Simplifying
-5(3t + -4) + 4t = 6t + -8

Reorder the terms:
-5(-4 + 3t) + 4t = 6t + -8
(-4 * -5 + 3t * -5) + 4t = 6t + -8
(20 + -15t) + 4t = 6t + -8

Combine like terms: -15t + 4t = -11t
20 + -11t = 6t + -8

Reorder the terms:
20 + -11t = -8 + 6t

Solving
20 + -11t = -8 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
20 + -11t + -6t = -8 + 6t + -6t

Combine like terms: -11t + -6t = -17t
20 + -17t = -8 + 6t + -6t

Combine like terms: 6t + -6t = 0
20 + -17t = -8 + 0
20 + -17t = -8

Add '-20' to each side of the equation.
20 + -20 + -17t = -8 + -20

Combine like terms: 20 + -20 = 0
0 + -17t = -8 + -20
-17t = -8 + -20

Combine like terms: -8 + -20 = -28
-17t = -28

Divide each side by '-17'.
t = 1.647058824

Simplifying
t = 1.647058824

See similar equations:

| -5y=.4 | | 4(x-5)-5=-6+7.4-4x | | -82=c-5 | | -3+2x=5x-36 | | 3r-8=-24 | | F(X)=100(1.04)200 | | 3(z+4)+6= | | 82=u-63 | | 12+2x+4y= | | 200=100(1.04)x | | h-9.2=28 | | 34x+4=106 | | F(200)=100(1.04)x | | -134-10x=58+2x | | -87=9+x | | 6x^2+12x^2-7x= | | F(200)=100(1.04)200 | | X+7=1+7x | | -54=-42+n | | x+13y+8y= | | x+3-2x=75 | | 9*n=2.5 | | 2a+4a=1 | | Z+4(z+3)=15 | | 9=8y | | -46+12x=38+5x | | 20x-60=10x-10 | | 7x-a=6a | | 7+6x=-5x+95 | | 2(c+6)=5(5+12) | | 10x^2-30=5x^2+5 | | 6(x^2-10x+25)=1 |

Equations solver categories